Comparison of culture methodology for the detection of methicillin-resistant Staphylococcus pseudintermedius in clinical specimens collected from dogs - Saab, Matthew E. (J Vet Diagn Invest, 2017)
Methicillin-resistant Staphylococcus pseudintermedius (MRSP) has emerged as a major pathogen in dogs and has been implicated as a hospital-acquired pathogen in veterinary hospitals. We attempted to determine if selective culture methods will detect more MRSP when compared to the traditional culture methods in clinical samples from dogs in Atlantic Canada with a high risk for MRSP infection. Each sample was tested using 4 culture methods: traditional culture; mannitol salt agar with 2 μg/mL of oxacillin (MSAox); enrichment broth (EB) with MSAox; and EB with traditional culture. Detection of penicillin-binding protein 2’, via latex agglutination, was used as a confirmatory test for oxacillin resistance. We analyzed 741 samples from 556 dogs between February 2013 and April 2014. The prevalence of MRSP in samples detected by any method was estimated at 13.4% (95% CI: 11.1–16.0%). When the prevalence of MRSP was determined according to culture method, EB with MSAox detected the highest prevalence (11.2% [9.1–13.7%]), followed by EB with traditional (10.8% [8.8–13.2%]), traditional (10.1% [8.1–12.5%]), and MSAox (8.9% [7.1–11.2%]). The prevalence using the traditional culture method did not differ significantly from any of the 3 selective culture methods. Culture with MSAox detected significantly fewer MRSP than either of the EB methods. The addition of EB to current methodology is recommended, particularly for patients considered at high risk for MRSP infection.